PENGARUH PERSEPSI RISIKO, KUALITAS PELAYANAN DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PADA PERCETAKAN HANNA COMPUTER SITUBONDO DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL MODERATING - Trie Oetami; Ediyanto Ediyanto; Randika Fandiyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The printing business is one of the fields that has experienced very rapid technological developments along with the increasing public demand for print media. Business actors are required to be able to implement effective marketing strategies and continue to experience improvements in all aspects to attract consumer interest, so they are ready to face increasingly fierce competition. The purpose of this study is to analyze and test the Influence of Risk Perception, Service Quality and Digital Marketing on Purchasing Decisions at Hanna Computer Situbondo Printing with Consumer Trust as a Moderating Variable. The sampling technique uses Non-Probability Sampling. Data analysis and hypothesis testing in this study use the Structural Equation Model - Partical Least Square (PLS-SEM). The results of the hypothesis test using the Smart PLS 3.0 application. Showing that Service Quality has a positive and significant effect on Purchasing Decisions. Meanwhile, Risk Perception and Digital Marketing have a positive but insignificant effect on Purchasing Decisions. The Consumer Trust variable shows a significant role in moderating the relationship between Service Quality and Purchasing Decisions in the direction of strengthening the relationship. Meanwhile, the consumer trust variable does not show a significant role in moderating the relationship between risk perception and digital marketing on purchasing decisions, with the direction of weakening the relationship.